Antibodies to Low-Copy Number RBC Alloantigen Convert a Tolerogenic Stimulus to an Immunogenic Stimulus in Mice - Jash, Arijita; Usaneerungrueng, Chomkan; Howie, Heather L.; Qiu, Annie; Luckey, Chance John; Zimring, James C.; Hudson, Krystalyn E. (Frontiers in Immunology, 2021)
Red blood cells expressing alloantigens are well known to be capable of inducing robust humoral alloantibody responses both in transfusion and pregnancy. However, the majority of transfusion recipients and pregnant women never make alloantibodies, even after repeat exposure to foreign RBCs. More recently, RBCs have been used as a cellular therapeutic – very much like transfusion, engineered RBCs are highly immunogenic in some cases but not others. In animals models of both transfusion and RBC based therapeutics, RBCs that do not induce an immune response also cause tolerance. Despite a robust phenomenology, the mechanisms of what regulates immunity vs. tolerance to RBCs remains unclear. However, it has been reported that copy number of alloantigens on the RBCs is a critical factor, with a very low copy number causing non-responsiveness (in both humans and mice) and also leading to tolerance in mice. Recently, we reported that an IgG2c specific for an RBC antigen can substantially enhance the humoral immune response upon transfusion of RBCs expressing that antigen. Herein, we report that an IgG2c converts RBCs with low antigen copy number from a tolerogenic to an immunogenic stimulus. These findings report the first known stimulus that induces humoral alloimmunization to a low copy number RBC alloantigen and identify a previously undescribed molecular switch that has the ability to affect responder vs. non-responder phenotypes of transfusion recipients.